A qualitative study of the motivation behind the prevalence of materialism in male millennials - Raeburn, Caitlin (The IIE, 2020)
In today’s consumer market, the dominance of the consumers has been gradually shifted to millennials. Therefore, understanding their attitudes toward materialism has become increasingly significant, as most of millennial individuals possess purchasing power which makes them a lucrative market segment. The purpose of this study is to help researchers better understand the motivation behind the prevalence of materialism in male millennials. The researcher seeks to use this information as a preventative measure rather than treating individuals based on the negative outcomes related to materialism such as decreases in one’s happiness, personal well-being, and gratification with life. This research paper employs standardised open-ended interviews as the research instrument to achieve the research objectives. The sample consisted of five South African male millennials. Throughout the study, the findings have clearly revealed that motivation exists behind the prevalence of materialism in male millennials. It is found that materialism is influenced and stimulated by low self-esteem and success. However, materialism does not necessarily decrease well-being. The present study attempted to add to existing literature on the motivation of materialism in millennials by investigating the under-researched demographic variable being gender in this widely materialistic cohort.
Keywords: Male millennials; Materialism; Motivation